Защита строительных конструкций и технологического оборудования от коррозии: [справочник] - Орлов А. М. Анатолий Михайлович; Чекулаева Е. И. Евгения Ивановна; Соколов В. А. Виталий Алексеевич; Балалаев Г. А.; Гольденберг Н. Л. (Справочник строителя)
Авт. указаны на обороте тит. л.